Pengaruh Kualitas Produk, Kualitas Pelayanan dan Suasana Terhadap Keputusan Pembelian - Yuliana, Selvia Tri; Tuti, Meylani (Journal of Economics, Bussiness and Management Issues, 2024)
The objective of this study is to examine the impact of product quality, service quality, and restaurant ambiance on consumer purchasing behavior in the restaurant industry. The research population consists of consumers of the restaurant. The sample size consisted of 167 individuals who were selected using accidental sampling, which involved selecting individuals who were willing to respond to the author's questionnaire. Data was gathered during January and February of 2024. The data analysis technique employed was the Structure Equation Model, using the SmartPLS software. The research findings indicate that the three distinct research variables, namely product quality, service quality, and atmosphere, significantly impact customer purchase decisions in restaurants. This demonstrates the restaurant's success in enticing consumers to visit and ensuring their satisfaction once dining.